Hubungan Kualitas Tidur dengan Kejadian Hipertensi pada Lansia di Puskesmas Andalas Kota Padang - Tia, Siska Floren; Muslim, Burhan; Jepisa, Tomi (Jurusan Kesehatan Lingkungan Poltekkes Kemenkes Padang, 2023)
As the elderly get older, physiological functions can decrease due to degenerative processes (aging). In 2022-2023 Andalas Padang Health Center reached 14,914 people who had hypertension. The purpose of this study was to determine the relationship between sleep quality and the incidence of hypertension in the elderly at the Andalas Padang Health Center in 2023 Quantitative research method with cross sectional design. This research was conducted in March-August 2023, collecting data on June 12-21 2023. The population in this study were all elderly people who were treated at Andalas Padang Health Center. The sampling technique used the accidental sampling technique with a sample of 65 respondents. The data collection tool used the PSQI questionnaire and Spygmomanometer. Data were analyzed univariately and bivariately using the Chi-Square test. The results of the study were more than half, namely 61.5%, had poor sleep quality in the elderly, more than half, namely 56.9%, had hypertension in the elderly. There is a relationship between sleep quality and the incidence of hypertension in the elderly with a p-value of 0.000 at the Andalas Health Center in Padang City in 2023.